PENGGUNAAN KARTU KATA DAN GAMBAR UNTUK MENGENALKAN HURUF PADA ANAK KELOMPOK B2 DI PAUD TANWIRUL QULUB MATARAM - Wulandari, Evalia; Suarta, I Nyoman; Nurhasannah, Nurhasanah; Buahana, Baiq Nada (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2021)
This research was motivated by the results of observations at PAUD Tanwirul Qulub Mataram, related to the introduction of children's letters such as not yet recognizing letters and often confused about the letter b with letter d, letter p with letter q, and letter a with letter e. To overcome this, a fun learning media is needed so that the child's letter recognition develops optimally. The purpose of this study was to find out how to apply playing activities using the right word cards and pictures to introduce letters to group B children at PAUD Tanwirul Qulub Mataram. This type of research uses three stages of development. The subjects of the study were kindergarten children in group B2 aged 5-6 years, totaling 15 people. Data collection techniques using observation methods and data analysis using qualitative descriptive techniques. The steps in playing word and picture cards are: (a) introducing word and picture card games, (b) telling children how or steps in playing word and picture cards by practicing directly, (c) observing children's development during the game. , and (d) conduct discussions and evaluations. The results showed that the average results of student observations in learning to recognize children's letters using word cards and pictures increased from development I, which was 55.50%, development II, 68.60%, and the average percentage in development III was 84, 93% with an increase of 13.10% indicates an increase that occurs in development I to development II and 16.33% indicates an increase from development II to development III. Based on the results of this study, it can be concluded that using word cards and pictures can introduce letters to kindergarten group B2 children aged 5-6 years at PAUD Tanwirul Qulub Mataram.